The Implementation of Distance Learning Policy in The Covid-19 Pandemic Era Through The Blended Learning Method in Pancasila and Civics - Nika Nur Aliantika; Rahmat Rahmat; Prayoga Bestari (Department of Civic Education, 2021)
The implementation of remote policies is the answer from the Government to the problems in the world of education caused by the Covid-19 pandemic in Indonesia. The many limitations in implementing remote policies during this pandemic, cannot be separated from the problems that occur during the implementation process. Educators play an important role in the successful implementation of remotely, required to innovate and be creative in conveying learning amid all existing limitations. Therefore, this study aims to find out